Silver linings playbook [videorecording (DVD)] - Russell, David O., 1958-; Cooper, Bradley; Lawrence, Jennifer, 1990-; De Niro, Robert; Weaver, Jacki, 1947-; Kher, Anupam, 1955-; Quick, Matthew, 1973- (Anchor Bay Entertainment, 2013)
Based on the bestselling book by Matthew Quick, the riotous and poignant story of how a man who has lost everything, his house, his job, his wife, reconnects with himself and creates his own silver linings from the bonds he forms with his family and friends.